Studi Literatur: Implementasi Dan Tantangan Penilaian Otentik Dalam Pembelajaran Tematik Di Sekolah Dasar - M. Erwin Deri Saputra; Nabila Saputri; Siti Nurhalisa; Karimah Dewi Yulianita; Amanda Olivia (Jurnal Karya Ilmiah Pendidik dan Praktisi SD&MI (JKIPP), 2025)
Authentic assessment in thematic learning in primary schools is an important approach to assessing students’ competencies thoroughly, not only on cognitive aspects but also affective and psychomotor. This assessment is relevant to Curriculum 2013 as it focuses on real tasks that reflect the application of knowledge and skills in everyday life. This research aims to describe the implementation of authentic assessment and identify challenges in its application in primary schools through a literature study. The method used was a literature study with an inductive approach, referring to relevant books, journals and online sources. The results of the study show that the implementation of authentic assessment has been running quite well with the use of various techniques such as portfolios, projects, observations, and written tests. However, the implementation still faces obstacles, such as time constraints, format complexity, and teachers’ lack of understanding of the concepts and techniques of authentic assessment. Therefore, continuous training and format simplification are needed so that authentic assessment can be implemented optimally and effectively in supporting meaningful learning